USE OF AI TOOLS IN DEVELOPING RESEARCH PROPOSALS AMONG PRE-SERVICE SCIENCE TEACHERS: A CASE STUDY - Hamzah, Azlina Amir (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The integration of Artificial Intelligence (AI) tools into academic research has become increasingly prevalent among higher education students. This case study explores how pre-service science teachers at Penang Teachers’ Training Institute utilise AI tools during the development of research proposals in the "Fundamental Research in Science Education" course. A mixed-methods questionnaire was used to explore AI usage patterns, perceived benefits and challenges, and ethical practices. Findings revealed that all students (100%) used ChatGPT, with 53.8% using it daily and 84.6% integrating AI-generated content for less than half their proposals. The data reveals that 76.9% used AI primarily for first drafts, 69.2% for topic exploration, and 53.8% for grammar checking. Students reported high perceived benefits, with 84.6% agreeing that AI enhanced proposal quality, 76.9% cited time savings, and 76.9% found it helpful for idea generation. However, the major challenges emerged with 76.9% encountering inaccurate information and 15.4% noting AI’s limited understanding of specialised scientific concepts. Students exhibited strong ethical awareness, with all participants disclosing AI use to instructors, demonstrating transparency. Although only 38.5% expressed full trust in AI outputs, 84.6% actively verified content using academic sources. Open-ended responses further highlighted AI’s role in refining language, generating ideas, and clarifying research focus. The study concludes that pre-service science teachers engage thoughtfully with AI tools as supplementary academic supports rather than replacements for critical thinking. It also highlights the importance of integrating AI literacy, ethical guidelines, and institutional support into teacher education programs to foster responsible and effective AI engagement in academic work.